"Just because you have a land claim, that doesn't mean everything's going to fall in place": An Inuit social struggle for fishery access and well-being. (June 2022) - Snook, Jamie; Cunsolo, Ashlee; Ford, James; Furgal, Chris; Jones-Bitton, Andria; Harper, Sherilee
Abstract: Commercial fishing supports coastal communities around the world and fishing livelihoods are often interwoven into local societies, including culture, identity, knowledges, and economies, particularly for many Indigenous Peoples globally. Through a case study with co-management board members in Nunatsiavut, Labrador, Canada, we explore how access to commercial fisheries is a determinant of Inuit well-being. Interviews with fisheries co-managers were conducted and analysed deductively and inductively using a conceptual well-being framework to characterize the ways in which commercial fisheries intersect with Inuit well-being. Our results highlight how commercial fisheries in Nunatsiavut have been a longstanding way of life, with multiple familial connections, and are interwoven with the social, economic, and political components of Indigenous culture and identity. Participants described how the fishing livelihood in Nunatsiavut was put at risk due to overfishing by foreign fleets who exploited Inuit waters during the cod fishery's formative years. Extensive narrative about fisher committees and community organizing highlighted how political participation and self-determination efforts in the 1970 s led to a measure of sustainability through new Northern Shrimp access. Despite periodic success stories, the Inuit commercial fishery remains in a social struggle. The results show how the fishery has continued with multiple injustices and forms of inequity. The combination of events over time, shared through stories, highlight that these small-scale Inuit fisheries were subject to ocean grabbing or ocean dispossession. Based on these results, future research that facilitates an Inuit vision of Nunatsiavut's fishing sector is critical, and reclamation policies that facilitate new pathways forward for reconciliation to centre Inuit well-being are needed. Furthermore, these results illustrate how Inuit identified well-being indicators could be adopted for immediate baseline monitoring and to measure progress.